Human Vision Reconstructs Time to Satisfy Causal Constraints. (February 2022) - Bechlivanidis, Christos; Buehner, Marc J.; Tecwyn, Emma C.; Lagnado, David A.; Hoerl, Christoph; McCormack, Teresa
The goal of perception is to infer the most plausible source of sensory stimulation. Unisensory perception of temporal order, however, appears to require no inference, because the order of events can be uniquely determined from the order in which sensory signals arrive. Here, we demonstrate a novel perceptual illusion that casts doubt on this intuition: In three experiments ( N = 607), the experienced event timings were determined by causality in real time. Adult participants viewed a simple three-item sequence, ACB, which is typically remembered as ABC in line with principles of causality. When asked to indicate the time at which events B and C occurred, participants' points of subjective simultaneity shifted so that the assumed cause B appeared earlier and the assumed effect C later, despite participants' full attention and repeated viewings. This first demonstration of causality reversing perceived temporal order cannot be explained by postperceptual distortion, lapsed attention, or saccades.